Union wage demands with footloose firms - Damiaan Persyn (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
This paper analyses the wage demands of a sector-level monopoly union facing internationally mobile firms. A simple two-country economic geography model is used to describe how firms relocate in function of international di erences in production costs and market size. The union sets wages in function of the firm level labour demand elasticity and the responsiveness of firms to relocate internationally. If countries are suffciently symmetric lower foreign wages and lower trade costs necessarily lead to lower union wage demands. With asymmetric countries these intuitive properties do not always hold. But even for symmetric countries it holds that small increases in market size or trade costs makes union wages more sensitive to the foreign wage level.
Keywords: J50; J31; F16; 330; Unions; globalisation; economic geography; Gewerkschaftspolitik; Lohn; Multinationales Unternehmen; Standortwahl; Wirtschaftsgeographie; Theorie